2019
DOI: 10.1155/2019/5620989
|View full text |Cite
|
Sign up to set email alerts
|

The Green Synthesis of MgO Nano-Flowers Using Rosmarinus officinalis L. (Rosemary) and the Antibacterial Activities against Xanthomonas oryzae pv. oryzae

Abstract: Recently, the use of herbs in the agriculture and food industry has increased significantly. In particular, Rosmarinus officinalis L. extracts have been reported to have strong antibacterial properties, which depend on their chemical composition. The present study displayed a biological method for synthesis of magnesium oxide (MgO) nano-flowers. The nano-flowers are developed without using any catalyst agent. Aqueous Rosemary extract was used to synthesize MgO nano-flowers (MgONFs) in stirring conditions and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 35 publications
4
84
0
Order By: Relevance
“…Various metals nanoparticles have been widely applied in agriculture due to their distinctive features such as antimicrobial activity, catalytic activity, magnetic and electrical properties [11,12]. Furthermore, several studies have demonstrated that metal nanoparticles have been well documented as fungicides [10,13]. For example, silver nanoparticles (AgNPs) have been shown to significantly inhibit the hyphal growth of a variety of foliar and soil-borne plant pathogen [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Various metals nanoparticles have been widely applied in agriculture due to their distinctive features such as antimicrobial activity, catalytic activity, magnetic and electrical properties [11,12]. Furthermore, several studies have demonstrated that metal nanoparticles have been well documented as fungicides [10,13]. For example, silver nanoparticles (AgNPs) have been shown to significantly inhibit the hyphal growth of a variety of foliar and soil-borne plant pathogen [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This, they suggested was due the more efficient penetration of the MgONPs into the seed coat to promote Mg content and water uptake needed for germination. Abdallah et al [6] synthesized MgO nano-flowers using aqueous extracts from Rosmarinus officinalis L. (Rosemary) flowers as the reducing agent. The obtained MgO nano-flowers showed significant antimicrobial effect against Xanthomonas oryzae pv.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoparticles based on titanium (Ti), cadmium (Cd), copper (Cu), iron (Fe), zinc (Zn), and magnesium (Mg), etc., have been emerging as a new class, owing to their exclusive applications in Nanomaterials 2020, 10, 766 6 of 16 research (Table 4). Rosemary extract (Rosmarinus officinalis L.) was used in MgO nano-flower synthesis in a stirring situation at 70 • C for 4 h [86]. Marigold flower (Tageta sp.)…”
Section: Other Nanoparticlesmentioning
confidence: 99%
“…In GC-MS analysis, the oleic acid in the flower extract was found to act as a reducing and capping agent, and the presence of oleic acid stabilized ZnO NPs, showing antibacterial activity against both Gram-positive E. faecium and Gram-negative E. coli bacteria. Abdallah et al (2019) found that magnesium oxide (MgO) NPs formed from the flower extract of Rosmarinus officinalis L. showed a strong inhibitory effect against biofilms of a rice pathogen, Xanthomonas oryzae pv. oryzae strain GZ 0005 [86].…”
Section: Antibacterial Activity Of Flower-derived Npsmentioning
confidence: 99%
See 1 more Smart Citation